THE IMPORTANCE OF ENGLISH CLUB: A CASE AT ENGLISH EDUCATION STUDY PROGRAM UNIVERSITAS MUHAMMADIYAH PALEMBANG - Fitriany, Sonia; Yuliani, Sri; Sulaiman, Masagus; Rositasari, Tri (English Community Journal, 2021)
The title of this study is The Importance of English Club: A Case at English Education Study Program Universitas Muhammadiyah Palembang. The objective of this study was to know the importance of English club to improve students’ English ability. This research was regarded on a qualitative study. The researcher used questionnaire to collecting the data and used the percentage analysis to analyze the data. The population of this study was the entire students of English education study program Universitas Muhammadiyah Palembang. Then 47 students from the fourth semester students were taken as the sample by using convenience sampling. The questionnaire consisted of 20 items. The result of this study was dominantly students who chose agree. Students think that English club can be useful to improve their English ability, especially in speaking skills. After joining the English club,the students are able to organize their ideas for speaking, more comfortable in speaking English, putting less effort to understand and willing to communicate in English.